Sternocleidomastoid-Clavicle Myoosseus Flap in Patient with Plate Displacement Post Resection and Reconstruction of Ameloblastoma - Natawidjaja, Ronald; Setiawan, Gede Budhi (JBN (Jurnal Bedah Nasional); Vol 2 No 1 (2018): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2018.v02.i01.p03, 2018)
Background: ameloblastoma is a common tumor found in head and neck disorder. The definitive treatment include resection of tumor and reconstruction for filling the large defect which left after tumor resection. The reconstruction option which can be done is flap method. In this case, we used sternocleidomastoid-clavicle myoosseus flap in our patient with post traumatic plate displacement post resection and reconstruction of ameloblastoma. Case: a 22-year-old woman presented with unstability of jaw after hitting her chin to the table since 3 days prior to admission. On 2011, she had history of ameloblastoma which got resected and reconstructed with fibular graft and plate in the same year. While the plate seemed to be broken, she was managed with plate removal and reconstruct with sternocleidomastoid-clavicle myoosseus flap. Post operation, patient managed with gradual diet from liquid to solid. Observation Post Operation Day (POD) 3, flap is vital. Patient is discharged on POD 7 and visit as outpatient every 3-5 days until POD 14. Finally, we remove the suture, operation scar is good, and the flap is vital during one year follow up. Conclusion: sternocleidomastoid-clavicle myoosseus flap is practical and safe procedure, which can be used as alternative option in  mandible reconstruction.